2005
DOI: 10.1089/vbz.2005.5.110
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Associated withBartonella vinsoniisubsp.berkhoffiiSeropositivity in Free-Ranging Coyotes from Northern California

Abstract: Bartonella vinsonii subsp. berkhoffii is a newly recognized pathogen of domestic dogs and humans. Coyotes (Canis latrans) are considered an important reservoir of this bacterium in the western United States, but its vectors are still unknown. Our objective was to identify environmental factors associated with Bartonella antibody prevalence in 239 coyotes from northern California, using an enzyme-linked immunosorbent assay. In addition, associations were evaluated between B. v. berkhoffii and two pathogens with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Results from proportional odds and adjacent categories models suggested that dogs with either D. immitis infection or A. (1). Interestingly, primarily outdoor dogs were not found to be more likely to have elevated Bartonella IFA titers than other dogs, and flea control was not protective against Bartonella exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Results from proportional odds and adjacent categories models suggested that dogs with either D. immitis infection or A. (1). Interestingly, primarily outdoor dogs were not found to be more likely to have elevated Bartonella IFA titers than other dogs, and flea control was not protective against Bartonella exposure.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the long-debated capability of ticks to serve as vectors for Bartonella has recently been demonstrated (354), and biting flies are known to play an important role in the transmission of Bartonella among ruminants where they are predominant bloodsucking parasites (122,279). Coincident with the prevalence of the common arthropod vectors, the Bartonella infection rate among mammals is usually higher in warm, humid areas than in cold, arid ones (29,206) and higher in wildlife than in domestic animals (e.g., 15 to 30% in pet cats [91,166,167] compared to up to 50% in feral cats [173]). The relationship between Bartonella and the different vectors has been comprehensively reviewed elsewhere (89).…”
Section: Host Specificitymentioning
confidence: 99%
“…A more recent study performed by Beldomenico et al . (2005) established a strong statistical correlation between An.…”
Section: Clinical Studies and Serosurveys In Cats Dogs And Coyotesmentioning
confidence: 99%